2015
DOI: 10.1007/s11673-015-9642-8
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Ethics in Commercial Surrogacy: Decision-Making in IVF Clinics in New Delhi, India

Abstract: As a neo-liberal economy, India has become one of the new health tourism destinations, with commercial gestational surrogacy as an expanding market. Yet the Indian Assisted Reproductive Technology (ART) Bill has been pending for five years, and the guidelines issued by the Indian Council of Medical Research are somewhat vague and contradictory, resulting in self-regulated practices of fertility clinics. This paper broadly looks at clinical ethics in reproduction in the practice of surrogacy and decision-making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Women's bodies have become consumer commodities for the huge reproductive industry, where the agents, and women themselves, prepare and groom their bodies to increase their market value, not knowing the risks involved (Tanderup et al, 2015b) and the long term impacts on their bodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's bodies have become consumer commodities for the huge reproductive industry, where the agents, and women themselves, prepare and groom their bodies to increase their market value, not knowing the risks involved (Tanderup et al, 2015b) and the long term impacts on their bodies.…”
Section: Resultsmentioning
confidence: 99%
“…There are only the guidelines of the Indian Council of Medical Research and the Ministry of Health and Family Welfare, or rather, Indian Government guidelinesthe "National Guidelines for Accreditation, Supervision and Regulation of ART Clinics in India" (2005)to follow, but these are merely guidelines and are not mandatory. These guidelines have little constitutional validity in terms of enforcement, and studies have shown clear violations of these guidelines (Team S.A.M.A., 2000;Tanderup, Reddy, Patel, & Nielsen, 2015b). Nevertheless, the guidelines are strikingly recalled by doctors and embryologists during interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Such a cultural taming of the ethical debate must be understood as a result of negotiating between the local and global context in which such debates are evolving and -at least for a particular moment in time -are fixable as culturally 'significant.' From a distant, comparative view there gleam some peculiarities: for instance, Indian sociologists have pointed out, despite critiques of the large economic and caste disparities, that it would be important to see the agency and opportunities for self-determination for surrogates, even in situations of commercial surrogacy (Tanderup et al 2015). In Germany, the agency of surrogates is rarely considered as leading point but ethicists have emphasized rather the 'best interest of the child' as a criterion of legitimization.…”
Section: The Body As Local Inscription or As Globalmentioning
confidence: 99%
“…2,3,12,26,28,29,[36][37][38][39][40][41] In these countries, an initial cursory explanation is given to women about surrogacy and legal contracts. This constitutes predetermined legal and medical consent.…”
Section: Informed Consentmentioning
confidence: 99%